Assessing access barriers to maternal health care: measuring bypassing to identify health centre needs in rural Uganda - Parkhurst, Justin O.; Ssengooba, Freddie (Health policy and planning, 2009)
In low income countries, several barriers exist to the use of health services for child delivery, including distance, transportation, informal costs or low perceived quality. Yet there is rarely information about which barriers are more or less important to the use of a given health facility. This study assessed the relative importance of different barriers to maternal health facility use in rural Uganda through the use of simple indicators based on locally available data. Methods Data from public health facilities performing deliveries in a rural district were used along with census information to construct a set of indicators useful for diagnosing barriers to delivery service use. Indicators included the number of facility-based deliveries per 1000 women served, the proportion of users from a facility’s local area, and a new indicator, the ‘bypassing ratio’, defined as the number of women from a facility’s local area who delivered in other facilities, divided by the number of local women using the facility itself. Results Numbers of deliveries varied greatly between facilities of the same level. A few very low use facilities saw over 75% of women come from the local area, while other facilities services attracted a large majority of women from other areas. The phenomenon of bypassing provides additional insight into the relative importance of distance or transport as opposed to internal facility factors preventing use.
Keywords: Maternal health; access barriers; bypassing; Uganda; health service use